Separator for electrochemical device and method for producing same
A modified porous base film with a functional layer of organic and inorganic materials addresses the issues of low conductivity and wettability in lithium-ion battery separators, enhancing thermal stability and safety.
Patent Information
- Application Number
- JP2022571259
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-21
- Filing Date
- 2021-03-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-03-11
AI Technical Summary
Conventional lithium-ion battery separators exhibit low ionic conductivity, low wettability, and poor thermal stability, which affect battery safety and performance.
A modified porous base film with a functional layer comprising a composite of organic and inorganic materials, including conductive lithium ion-containing compounds like LiAlSi2O6, Li2FeSiO4, and LiFePO4, is used, along with a sol-gel-hydrothermal method to enhance ionic conductivity and adhesion.
The modified separator improves wettability, reduces thermal shrinkage, and enhances ionic conductivity, leading to improved thermal and physicochemical performance, thereby increasing battery safety and cycling performance.
Smart Images

Figure 0007621383000003 
Figure 0007621383000004 
Figure 0007621383000005
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to separators for electrochemical devices and methods for making same. [Background technology]
[0002] Lithium-ion batteries, as a new rechargeable and renewable energy source, have the advantages of high operating voltage, light weight, and high energy density. They are widely used in fields such as power tools, digital cameras, mobile phones, and laptops, and are showing a strong development trend.
[0003] The separator is one of the key assemblies of a lithium ion battery, which is used to prevent short circuit caused by direct contact between the positive and negative electrodes by isolating the positive and negative electrodes of the battery, and is required to have good lithium ion permeability and close the ion channel when the temperature is too high during the operation of the battery to ensure the safety of the battery. Therefore, the separator plays an important role in the safety of the lithium ion battery.
[0004] Lithium ion conductors have the characteristics of high conductivity, low activation energy, and the most negative electrode potential. 14 ZnGeO4), and LiTi2P3O 12 Many studies have been conducted on inorganic lithium ion conductors, such as solid solutions based on inorganic lithium ion conductors. However, inorganic lithium ion conductors have no practical value due to their different electrical conductivity, low decomposition voltage, and inability to withstand corrosion of metallic lithium. Organic lithium ion conductors discovered later, such as complexes of polymers (e.g., polyoxyethylene) and base metal salts (e.g., LiCF3SO3), have lower electrical conductivity than inorganic lithium ion conductors, but can be easily processed into thin films, making up for the lack of electrical conductivity, and have excellent viscoelasticity. As a result, they are widely used as separator materials for high-energy lithium batteries, and are used to make high-specific-energy, large-capacity batteries and high-temperature fuel cells.
[0005] Currently, the separators widely used in lithium batteries are mainly polyolefin-based melt-drawn separators, and the shutdown effect of these materials helps improve safety when the battery heats up. However, conventional commercial PE / PP separators have low wettability to electrolyte, low liquid retention, low ionic conductivity, and severe thermal shrinkage. These problems affect the processing, cycle, and multiplication performance of the battery, as well as safety at high temperatures. Coating a polymer separator with ceramic paste to improve the heat resistance and mechanical performance of the separator and thereby improve the safety of the separator has been widely applied and studied. However, there is no mention of improving the permeability of lithium ions by modifying the base film. Therefore, the field needs a separator for electrochemical devices that improves the safety of the battery and has better ionic conductivity. Summary of the Invention [Problem to be solved by the invention]
[0006] In view of the above, it is expected that the present invention provides a separator for an electrochemical device and a method for manufacturing the same, which solves the drawbacks of conventional separators, such as low ionic conductivity and low wettability, and provides the separator with good adhesion and heat resistance. [Means for solving the problem]
[0007] In order to achieve the above objectives, the technical solution of the present invention is realized as follows:
[0008] The present invention provides a separator for an electrochemical device, comprising a modified porous base film and a functional layer provided on at least one surface of the modified porous base film, the functional layer containing a slurry of a composite of an organic material and an inorganic material, and the modified porous base film containing particles of a conductive lithium ion-containing compound. Additionally, the conductive lithium ion-containing compounds include LiAlSi2O6, Li2FeSiO4, and LiFePO4. Furthermore, the particle size of the conductive lithium ion-containing compound is 5 to 20 nm. Furthermore, the particle size of the conductive lithium ion-containing compound is 10 to 20 nm.
[0009] Furthermore, the constituent mass parts of the raw materials of the slurry containing the complex of an organic substance and an inorganic substance are 5 to 80 parts of organic polymer, 3 to 40 parts of inorganic substance, and 50 to 100 parts of organic solvent.
[0010] Moreover, the organic polymer is polyvinylidene fluoride and has a molecular weight of 100,000 to 1,000,000, and the slurry containing the composite of an organic substance and an inorganic substance has a solid content of the polyvinylidene fluoride of 5 to 20 wt %. In turn, the inorganic materials include aluminum trioxide, boehmite, silicon dioxide, titanium dioxide, barium sulfate, calcium carbonate, and calcium oxide.
[0011] Moreover, the organic solvent is selected from one or a combination of more than one of N-methylpyrrolidone (NMP), dimethylacetamide (DMAC), acetone, N,N-dimethylformamide (DMF), and dimethylsulfoxide (DMSO).
[0012] The present invention further provides a method for preparing the above-mentioned modified porous base film by sol-gel-hydrothermal method.Specifically, after corona pretreatment of unmodified porous base film, pass through a tank of saturated aqueous solution of conductive lithium ion-containing compound, and after water treatment, carry out drying treatment in oven, and obtain the above-mentioned modified porous base film containing particles of conductive lithium ion-containing compound after drying.
[0013] Furthermore, the speed at which the saturated aqueous solution of the conductive lithium ion-containing compound passes through the tank is 5 m / min. The present invention provides a method for producing a separator for the electrochemical device, comprising the steps of: Step S1 of preparing the modified porous base film,
[0014] Step S1: after corona pretreatment of the unmodified porous base film, the film is passed through a tank of a saturated aqueous solution of a conductive lithium-ion-containing compound, and then the film is dried in an oven after water treatment, and the modified porous base film is obtained after drying;
[0015] A step S2 of preparing the slurry containing a composite of an organic substance and an inorganic substance,
[0016] Step S2 of mechanically stirring and mixing the organic polymer and the organic solvent according to the ratio to dissolve the organic polymer and the organic solvent, mechanically stirring and mixing the inorganic substance and the organic solvent according to the ratio to homogeneously mix the completely dissolved organic solution and the homogeneously mixed inorganic substance, and then obtaining the slurry;
[0017] There is further provided a method for preparing a separator for the electrochemical device, comprising: a step S3 of applying the slurry to at least one surface of the modified porous base film to form a functional layer. Effect of the Invention
[0018] The beneficial effects of the present invention are as follows:
[0019] 1) The present invention provides a separator for an electrochemical device and a method for preparing the same, which prepares a conductive lithium ion-containing compound by a sol-gel-hydrothermal method, and embeds small particles of the conductive lithium ion-containing compound into the base film of the separator, thereby greatly improving the ionic conductivity of the separator, greatly reducing the internal resistance of the electrochemical device in which the separator is used, and greatly improving the cycle performance of the device, thereby realizing excellent electrochemical performance of the separator;
[0020] 2) The present invention provides a separator for electrochemical devices and a method for preparing the same. By modifying the base film, the wettability is significantly improved, and the separator achieves excellent physicochemical performance;
[0021] 3) The present invention provides a separator for an electrochemical device and a method for preparing the same, in which a slurry containing an organic and inorganic composite is applied to one or both sides of a modified base film, thereby reducing the thermal shrinkage rate of the separator, improving adhesion, and improving the shortcoming of the separator's low wettability, thereby realizing the separator's excellent thermal and physicochemical performance. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a method for fabricating a separator structure for a battery provided by the present invention. [Diagram 2] FIG. 2 is a schematic diagram of a separator structure of an electrochemical device according to some embodiments of the present invention. [Diagram 3] FIG. 3 is a schematic diagram of a separator structure of an electrochemical device according to some other embodiments of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. It should be understood that the embodiments of the present invention described herein are merely for the purpose of explaining and interpreting the present invention, and do not limit the present invention.
[0024] The range endpoints and any values disclosed herein should not be construed as being limited to the exact range or value, and should be understood to include any values close to those ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and the single point value, and the single point values can be combined with one another to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein.
[0025] The present invention provides a separator for an electrochemical device, comprising a modified porous base film 100 and a functional layer 101 provided on at least one surface of the modified porous base film 100, the functional layer 101 containing a slurry of a complex of an organic material and an inorganic material, and the modified porous base film 100 containing particles of a conductive lithium ion-containing compound.
[0026] Specifically, the conductive lithium ion-containing compounds include LiAlSi2O6, Li2FeSiO4, and LiFePO4. Specifically, the particle size of the conductive lithium ion-containing compound is 5 to 20 nm.
[0027] Preferably, the particles of the conductive lithium ion-containing compound have a particle size of 10 to 20 nm.
[0028] The present invention further provides a slurry for preparing a functional layer of a separator of a lithium ion battery, comprising, in parts by weight: 5 parts to 80 parts of an organic polymer; 3 to 40 parts inorganic matter; and 50 to 100 parts of an organic solvent.
[0029] Specifically, the organic polymer is polyvinylidene fluoride, has a molecular weight of 100,000 to 1,000,000, and has a solid content of 5 to 20 wt %.
[0030] Preferably, the minerals include aluminum trioxide, boehmite, silicon dioxide, titanium dioxide, barium sulfate, calcium carbonate, and calcium oxide.
[0031] Preferably, the organic solvent is selected from one or a combination of two or more of NMP, DMAC, acetone, DMF, and DMSO.
[0032] In some embodiments of the present invention, the base film is a PE base film, which may be any base film applied in the field to prepare lithium ion battery separators, such as a generally linear low density polyethylene base film. In some embodiments of the present invention, the base film has a thickness of 5 to 25 μm, and the functional layer has a thickness of 1 to 4 μm.
[0033] The present invention further provides a method for preparing lithium block ion nanoconductor by sol-gel-hydrothermal method and modifying the above-mentioned porous base film.The specific implementation method is that unmodified porous base film is corona pre-treated, then immersed in the solution containing nano-conductive lithium ion, and after the solution is completely immersed in the base film, it is dried in an oven to obtain the modified base film 100 with conductive ion compound in which small-sized lithium particles are embedded.
[0034] Specifically, the speed at which the conductive lithium ion-containing compound passes through a tank of a saturated aqueous solution (i.e., the speed at which the conductive lithium ion-containing compound is completely immersed and separated) is 5 m / min. The present invention provides a method for producing a separator for the electrochemical device, comprising the steps of: Step S1 of preparing the modified porous base film 100,
[0035] Step S1: the unmodified porous base film is subjected to corona pretreatment, then passed through a tank of a saturated aqueous solution of a conductive lithium ion-containing compound, and then subjected to drying treatment in an oven after water treatment, and after drying, the modified porous base film 100 is obtained; A step S2 of preparing the slurry containing a composite of an organic substance and an inorganic substance,
[0036] Step S2 of mechanically stirring and mixing the organic polymer and the organic solvent according to the ratio to dissolve the organic polymer and the organic solvent, mechanically stirring and mixing the inorganic substance and the organic solvent according to the ratio to homogeneously mix the completely dissolved organic solution and the homogeneously mixed inorganic substance, and then obtaining the slurry;
[0037] There is further provided a method for preparing a separator for the electrochemical device, comprising: a step S3 of applying the slurry to at least one surface of the modified porous base film to form a functional layer 101. In some embodiments of the present invention, the slurry is applied to one side of the base film. In some embodiments of the present invention, the slurry is applied to both sides of the base film.
[0038] In some embodiments of the present invention, the coating layer is obtained by coating a slurry, water treating, and drying the coating layer, in which the coating film is applied and then introduced into a tank, where the water in the tank extracts the solvent in the slurry, and then the slurry hardens into a base film to form the coating layer.
[0039] Preferably, the drying temperature is 50 to 60°C. The present invention further provides a separator for a lithium ion battery made by the above method.
[0040] The present invention further provides a lithium ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator as the separator of the electrochemical device according to the present invention.
[0041] The electrolyte is well known to those skilled in the art and generally comprises an electrolyte lithium salt and an organic solvent. Here, the electrolyte lithium salt is a dissociable lithium salt, and may be selected from at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), and lithium tetrafluoroborate (LiBF4), etc. The organic solvent may be selected from at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), vinylene carbonate (VC), etc.
[0042] The positive electrode is made by preparing a positive electrode material for lithium ion batteries, a conductive agent, and an adhesive into a slurry and applying the slurry onto an aluminum foil. The positive electrode material used includes any positive electrode material used in lithium ion batteries, such as at least one of lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), and lithium ferrous phosphate (LiFePO4).
[0043] The negative electrode is fabricated by preparing a negative electrode material for lithium ion batteries, a conductive agent, and an adhesive into a slurry and applying the slurry onto a copper foil. The negative electrode material used includes any negative electrode material used in lithium ion batteries, such as at least one of graphite, soft carbon, and hard carbon.
[0044] The main improvement of the lithium ion battery provided by the present invention is that a new lithium ion battery separator is adopted, and the arrangement (connection) of the positive electrode, negative electrode, battery separator and electrolyte may be the same as in the prior art, which is well known to those skilled in the art and will not be described again here.
[0045] The method for producing a lithium ion battery provided by the present invention comprises the steps of sequentially stacking or winding a positive electrode, a separator as the separator of the electrochemical device of the present invention, and a negative electrode around a core, and then injecting an electrolyte into the core and sealing it.
[0046] The materials and configurations of the positive electrode, negative electrode, and electrolyte have already been described, and will not be repeated here. The present invention will now be described in detail with reference to examples. In the following examples and comparative examples, the physicochemical parameters of the raw materials are as follows:
[0047] LiAlSi2O6 is a nano-inorganic powder obtained by strongly dispersing and gelling Al(ClO4)3, Si(OC2H5)4, C2H5OH, LiOH, etc., and then forming a gel through a hydrothermal reaction at 120°C. The gel is then dried, polished, pressed into a sheet, and subjected to a solid-state reaction at high temperature.
[0048] Li2FeSiO4 is a powder obtained by dissolving CH3COOLi·2H2O, C6H5FeO7·5H2O, (C2H5O)4Si, and C6H8O7·H2O at 80°C, stirring, and flowing back to obtain a gel, which is then dried, polished, pressed into a sheet, and subjected to a solid-state reaction at high temperature.
[0049] Polyvinylidene fluoride (PVDF) is a powder or granule that is translucent or white in appearance. Aluminum oxide is a powder that is white in appearance.
[0050] Dimethylacetamide (DMAC) is a colorless, transparent liquid with low toxicity and flammability, and can be mixed with any organic solvent, such as water, alcohol, ether, ester, benzene, chloroform, and aromatic compounds. All of the above raw materials can be purchased from the market or prepared by conventional methods. In the following examples and comparative examples, performance parameters are measured by the following methods.
[0051] (1) Measurement of separator thermal shrinkage Take a separator with an intact film surface and no abnormalities in appearance, cut it into a 100*100mm square, mark all four sides, and then bake it in an oven at 120℃ for 2 hours. Then take out the separator and measure the change in the length of the mark in the MD / TD direction of the separator after baking.
[0052] (2) Separator interface adhesion measurement A separator with an intact membrane surface and no abnormalities in appearance was taken, and punched out into a specimen 25 mm wide and 100 mm long. Two of the punched separator specimens were laminated together and hot pressed under conditions of a pressure of 1 MPa, a temperature of 100 degrees and a speed of 100 mm / min. The tensile strength (unit: N) of the two bonded separators was measured using a tensile machine, where adhesive strength = tensile strength / 0.025 (unit: N / m).
[0053] (3) Wettability measurement of separator Take a separator with a perfect membrane surface and no abnormality in appearance, cut it into a 100*100mm square, fix the edge of the separator flat, float the center of the separator, take 2μl of electrolyte and drop it onto the center of the separator, record the extension distance A of the droplet along the MD / TD directions on the separator at this time, and after 5min, record the extension distance B of the droplet along the MD / TD directions on the separator again at this time, where the wetting distance=(BA) / 2.
[0054] (4) Measurement of ionic conductivity of separator Cut out four circular separator samples with a diameter of φ50 mm, place them in the electrolyte, seal and soak for 1 h. Place the four separator samples in turn into the test mold and measure them by the electrochemical workstation to read the resistance values R1, R2, R3 and R4.
[0055] Surface resistance calculation By plotting a chart with the number of layers as the abscissa and the resistance value for different numbers of layers as the ordinate, the slope A of the curve was calculated and the thickness D of the separator was measured, where the sheet resistance R of the sample is A·S and the ionic conductivity of the separator is D / R, where S is the effective electrode area of the test.
[0056] (5) Measuring the internal resistance of lithium-ion batteries – Method for measuring internal resistance using AC voltage drop Since the battery actually corresponds to an active resistor, a fixed frequency and a fixed current are applied to the battery (currently, a frequency of 1 KHz and a small current of 50 mA are generally used), and the voltage is sampled and the internal resistance of the battery is calculated by the transport circuit through a series of processes such as rectification and filtering.
[0057] (6) Measurement of cycle performance of lithium-ion batteries Charge a lithium-ion battery at room temperature at a rate of 0.5C and discharge it at a rate of 0.5C for 500 cycles, and calculate its capacity retention according to the formula: Capacity retention = (battery capacity after 500 cycles / room temperature capacity of battery before cycling).
[0058] Example 1 1. 0.7 kg of polyvinylidene fluoride is put into 6.3 kg of DMAC solution and mechanically stirred until completely dissolved to obtain a transparent rubber-like solution a; 0.3 kg of aluminum oxide powder is put into 2.7 kg of DMAC solution and mechanically stirred until completely dispersed to obtain solution b; a and b are thoroughly stirred and uniformly stirred to obtain a composite slurry.
[0059] 2. Take a 12um PE base film, and after corona pretreatment, pass it through a tank of saturated aqueous solution containing LiAlSi2O6 (speed is 5m / min). After water treatment, dry it in an oven. After drying, obtain the base film 100 after modification treatment.
[0060] 3. Using the gravure roll coating method (the specific method of coating using the gravure roll is to pump the composite slurry to the gravure roll, then rotate the gravure roll to bring the material to the gravure roll and contact the modified base film 100, so that the composite slurry can be coated on the modified base film 100), the composite slurry is coated on one side of the modified base film 100 (the coating speed is 30m / min), and after water treatment, it is dried in a three-stage oven (the oven temperatures of each stage are 50°C, 60°C, and 55°C respectively). After drying, a double-coated lithium ion battery separator (as shown in Figure 3) is obtained, and the batch of separators is denoted as A, where the thickness of the coated lithium ion battery separator is 14μm, and the thickness of the coating layer is 2μm.
[0061] Example 2 1. 0.7 kg of polyvinylidene fluoride is put into 6.3 kg of DMAC solution and mechanically stirred until completely dissolved to obtain a transparent rubber-like solution a; 0.3 kg of aluminum oxide powder is put into 2.7 kg of DMAC solution and mechanically stirred until completely dispersed to obtain solution b; a and b are thoroughly stirred and uniformly stirred to obtain a composite slurry.
[0062] 2. Take a 12um PE base film, and after corona pretreatment, pass it through a tank of saturated aqueous solution containing LiAlSi2O6 (speed is 5m / min). After water treatment, dry it in an oven. After drying, obtain the base film 100 after modification treatment.
[0063] 3. Using the gravure roll coating method (the specific method of coating using the gravure roll is to pump the composite slurry to the gravure roll, then rotate the gravure roll to bring the material to the gravure roll and contact it with the modified base film 100, so that the composite slurry can be coated on the modified base film 100). Coat the composite slurry on both sides of the modified base film 100 (coating speed is 30m / min), and dry in a three-stage oven (the oven temperatures of each stage are 50°C, 60°C, and 55°C, respectively). After drying, a triple-coated lithium ion battery separator (as shown in Figure 2) is obtained, and the batch of separators is denoted as B, where the thickness of the coated lithium ion battery separator is 16μm, and the thickness of the double-sided coating layer is 2μm.
[0064] Example 3 1. 0.7 kg of polyvinylidene fluoride was added to 6.3 kg of DMAC solution and mechanically stirred until completely dissolved to obtain a transparent rubber-like PVDF solution.
[0065] 2. Take a 12um PE base film, and after corona pretreatment, pass it through a tank of saturated aqueous solution containing LiAlSi2O6 (speed is 5m / min). After water treatment, dry it in an oven. After drying, obtain the base film 100 after modification treatment.
[0066] 3. Using the gravure roll coating method (the specific method of coating using the gravure roll is to pump the rubbery PVDF solution to the gravure roll, then rotate the gravure roll to bring the material to the gravure roll and contact the modified base film 100, so that the rubbery PVDF solution can be coated on the modified base film 100). The rubbery PVDF solution is coated on both sides of the modified base film 100 (coating speed is 30m / min), and dried in a three-stage oven (the oven temperatures of each stage are 50°C, 60°C, and 55°C, respectively). After drying, a triple-coated lithium ion battery separator (as shown in Figure 2) is obtained, and the separator of this batch is denoted as C, where the thickness of the coated lithium ion battery separator is 16μm, and the thickness of the two-side coating layer is 2μm.
[0067] Comparative Example 1 1. 0.7 kg of polyvinylidene fluoride is put into 6.3 kg of DMAC solution and mechanically stirred until completely dissolved to obtain a transparent rubber-like solution a; 0.3 kg of aluminum oxide powder is put into 2.7 kg of DMAC solution and mechanically stirred until completely dispersed to obtain solution b; a and b are thoroughly stirred and uniformly stirred to obtain a composite slurry.
[0068] 2. Using a gravure roll coating method (the specific method of coating using a gravure roll is to pump the composite slurry to the gravure roll, then rotate the gravure roll to bring the material to the gravure roll and make it contact with the base film, so that the composite slurry can be coated on the base film), the composite slurry is coated on one side of the base film (coating speed is 30m / min), and after water treatment, it is dried in a three-stage oven (the oven temperatures for each stage are 50°C, 60°C, and 55°C respectively). After drying, a double-coated lithium ion battery separator is obtained, and the batch of separators is denoted as D, where the thickness of the coated lithium ion battery separator is 14μm, and the thickness of the coating layer is 2μm.
[0069] Comparative Example 2 1. 0.7 kg of polyvinylidene fluoride is put into 6.3 kg of DMAC solution and mechanically stirred until completely dissolved to obtain a transparent rubber-like solution a; 0.3 kg of aluminum oxide powder is put into 2.7 kg of DMAC solution and mechanically stirred until completely dispersed to obtain solution b; a and b are thoroughly stirred and uniformly stirred to obtain a composite slurry.
[0070] 2. Using a gravure roll coating method (the specific method of coating using a gravure roll is to pump the composite slurry to the gravure roll, then rotate the gravure roll to bring the material to the gravure roll and make it contact with the base film, so that the composite slurry can be coated on the base film), the composite slurry is coated on both sides of the base film (coating speed is 30m / min), and dried in a three-stage oven (the oven temperatures of each stage are 50°C, 60°C, and 55°C respectively). After drying, a double-coated lithium ion battery separator is obtained, and the batch of separators is denoted as E, where the thickness of the coated lithium ion battery separator is 16μm, and the thickness of the double-coated layers is 2μm.
[0071] Comparative Example 3 1. 0.7 kg of polyvinylidene fluoride was added to 6.3 kg of DMAC solution and mechanically stirred until completely dissolved to obtain a transparent rubber-like PVDF solution.
[0072] 2. Using the gravure roll coating method (the specific method of coating using the gravure roll is to pump the rubbery PVDF solution to the gravure roll, then rotate the gravure roll to bring the material to the gravure roll and make it contact with the base film, so that the rubbery PVDF solution can be coated on the base film), the rubbery PVDF solution is coated on both sides of the base film (coating speed is 30m / min), and dried in a three-stage oven (the oven temperatures of each stage are 50℃, 60℃, and 55℃ respectively). After drying, a double-coated lithium ion battery separator is obtained, and the batch of separators is denoted as F, where the thickness of the coated lithium ion battery separator is 16μm, and the thickness of the double-coated layers is 2μm.
[0073] The batteries are manufactured by a normal method for manufacturing batteries known to those skilled in the art (including steps such as stacking the positive electrode, separator, and negative electrode in order or winding them around a core, injecting an electrolyte into the core and sealing it, leaving it, forming it, and checking the capacity), and the batteries into which the separators of batches A, B, C, D, E, and F have been introduced are tracked and marked.
[0074] The separators in Examples 1 to 3 and Comparative Examples 1 to 3 were measured based on the above-mentioned methods for measuring performance parameters, and the results are recorded in Table 1.
[0075] From the batteries of separators of batches A, B, C, D, E, and F, five batteries (marked as A1-A5, B1-B5, C1-C5, D1-5, E1-E5, and F1-F5, respectively) are selected for each batch to carry out internal resistance and cycle performance measurements, and the results are recorded in Table 2.
[0076] Table 1. Separator performance measurements for six batches JPEG0007621383000001.jpg70170
[0077] Table 2 Battery performance measurements for six batches of separators JPEG0007621383000002.jpg205170
[0078] Referring to Tables 1 and 2, it can be seen from the comparison of Examples 1, 2, and 3 with Comparative Examples 1, 2, and 3 that after the functional layer according to the present invention is applied, the thermal shrinkage rate is greatly reduced, excellent thermal stability and adhesion performance are exhibited, the position of the separator and the pole pieces after the composite is more stable, and the safety performance of the battery is correspondingly greatly improved. In addition, the wettability is improved, the ionic conductivity is also improved, and the internal resistance of the battery is correspondingly slightly lowered, and the cycle performance is improved.
[0079] Referring to Tables 1 and 2, by comparing Examples 1, 2, and 3 with Comparative Examples 1, 2, and 3 in order, it can be seen that the modified base film of the present invention significantly improves wettability, significantly improves ionic conductivity, correspondingly significantly reduces the internal resistance of the battery, and significantly improves cycle performance. Therefore, the separator according to the present invention has excellent physicochemical properties, thermal properties and electrochemical properties, and has extremely high industrial applicability. The above description does not explain in detail the contents related to common knowledge, but it should be understood by those skilled in the art.
[0080] The above are merely some specific examples of the present invention, and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention should be included within the protection scope of the present invention. The technical scope of the present invention is not limited to the contents described in the specification, and should be determined based on the claims. [Explanation of symbols]
[0081] 100 Modified porous base film 101 Functional Layer S1~S3 Step 1~Step 3
Claims
1. 1. A method of making a separator for an electrochemical device, comprising: The unmodified porous base film is subjected to corona pretreatment, and then passed through a tank of a saturated aqueous solution of a conductive lithium ion-containing compound, and then dried in an oven after the water treatment, to obtain a modified porous base film containing particles of the conductive lithium ion-containing compound after drying; A step of preparing a slurry containing a composite of an organic substance and an inorganic substance, and applying the slurry to at least one surface of the modified porous base film to form a functional layer; the organic material is polyvinylidene fluoride; The inorganic material includes at least one of aluminum trioxide, boehmite, silicon dioxide, titanium dioxide, barium sulfate, calcium carbonate, and calcium oxide.
1. A method for producing a separator for an electrochemical device, comprising:
2. The conductive lithium ion-containing compound is LiAlSi 2 O 6 , Li 2 FeSiO 4 , and LiFePO 4 At least one of the following is included:
2. The method of claim 1 .
3. The particles of the conductive lithium ion-containing compound have a particle size of 5 to 20 nm.
2. The method of claim 1 .
4. The mass parts of the raw materials of the slurry containing the composite of an organic substance and an inorganic substance are 5 parts to 80 parts of polyvinylidene fluoride, 3 parts to 40 parts of the inorganic substance, and 50 parts to 100 parts of the organic solvent.
2. The method of claim 1 .
5. The molecular weight of polyvinylidene fluoride is 100,000 to 1,000,000; The solid content of the polyvinylidene fluoride in the slurry containing the organic and inorganic complex is 5 to 20 wt %.
5. The method of claim 4.
6. The organic solvent is selected from one or a combination of a plurality of N-methylpyrrolidone, dimethylacetamide, acetone, N,N-dimethylformamide, and dimethylsulfoxide.
5. The method of claim 4.
Citation Information
Patent Citations
Modified solid electrolyte membrane, preparation method thereof and lithium battery
CN109494390A
Composite materials and electrochemical batteries
JP2002529891A
Organic inorganic complex porous film and electrochemical element using the same
JP2011138780A
Method of producing laminated porous film, laminated porous film, and non-aqueous electrolytic solution secondary battery
JP2013223957A
Separation membrane and lithium-sulfur battery including the same
JP2016532992A